Engaging postgraduate students in preparing research proposals - Pramela Krish; Khazriyati Salehuddin; Norizan A. Razak (Penerbit Universiti Kebangsaan Malaysia, 2017)
Both foreign and local postgraduate candidates of Universiti Kebangsaan Malaysia come from diverse backgrounds and experiences. These students face several problems especially in writing the research proposals. Hence, to facilitate the process of writing a proposal, they are required to enrol in Research Methodology, a course that is made compulsory for all postgraduate students. This article presents a report on an action research that investigates the research skills of English as a Second Language postgraduates and their research journey while undergoing the Research Methodology course. Data was collected from their weekly journal entries and the interviews conducted on them. This data is also supported with the feedback by the Research Methodology course instructors during the proposal defense sessions. The findings suggest that although the students seemed enthusiastic when writing their proposals, they were not ready when faced with questions about research problems and approaches. It is found that these students did not read extensively to identify the gaps in their research and this hence, resulted in them facing difficulties to write a clear statement of the problem. This also led to poor formulation of their research questions. The findings will be beneficial for instructors and potential supervisors who aim to be better at teaching and supervising potential postgraduate students.